The necessary journey : making real progress on equity and inclusion - Washington, Ella F. (Ascent Audio, 2022)
"What does a workplace utopia look like to you?" This is the question Dr. Ella F. Washington asks company leaders, and often she hears about an ideal vision of an organization that values diversity and inclusion and wants employees to bring their whole selves to work. But how can you get there? Organizations have largely missed the mark when it comes to creating environments where all employees thrive in an equal and equitable way, because they treat diversity, equity, and inclusion (DEI) as a program that gets done rather than the necessary and difficult journey it is. The road to an inclusive workplace is a difficult one, but you can traverse it, and there's help along the way. Start here with stories of companies making the necessary journey, including Slack, PwC, Best Buy, Denny's, and many others. Hear from company leaders about their successes and failures, the times they were on the vanguard, and the moments they realized they had much more work to do. These are profiles in perseverance from people who are keen enough to recognize the need for inclusive workplaces and humble enough to know they're not there yet. Along the way, Washington provides a framework for thinking about where these companies are on their journeys and where you and your company may be too.